A combined surveillance program and quality register improves management of childhood disability. Issue 8 (10th April 2017) - Alriksson-Schmidt, Ann I.; Arner, Marianne; Westbom, Lena; Krumlinde-Sundholm, Lena; Nordmark, Eva; Rodby-Bousquet, Elisabet; Hägglund, Gunnar
Abstract: Purpose : To describe a concept for prevention of secondary conditions in individuals with chronic neuromuscular disabilities by using two Swedish developed follow-up-programmes for cerebral palsy (CP; CPUP) and myelomeningocele (MMC; MMCUP) respectively as examples. Method : This paper describes and outlines the rationale, development and implementation of CPUP and MMCUP. Results : Both programmes are multidisciplinary longitudinal follow-up programmes that simultaneously serve as national registries. The programmes are population-based and set in Swedish habilitation clinics. Most children (95%) born 2000 or later with CP are enrolled in CPUP and the recruitment of adults is underway. CPUP has also been implemented in Norway, Denmark, Iceland, Scotland and parts of Australia. In MMCUP, almost all children with MMC born 2007 or later participate and individuals of all ages are now invited. The registries provide epidemiological profiles associated with CP and MMC and platforms for population-based research and quality of care improvement. Conclusions : Through multidisciplinary follow-up and early detection of emerging complications individuals with CP or MMC can receive less complex and more effective interventions than if treatment is implemented at a later stage. Possibilities and challenges to design, implement and continuously run multidisciplinary secondary prevention follow-up programmes and quality registries for individuals with CP or MMC are described and discussed. Implications for rehabilitation: Individuals with disabilities such as cerebral palsy or myelomeningocele are at risk of developing secondary conditions. Multidisciplinary population-based longitudinal follow-up programmes seem effective in preventing certain types of secondary conditions.